EXPERIMENTAL RESEARCH OF THE FRIABLE LOAD OFFSETS’ EFFECT ON THE VEHICLES’ AXIAL CARGO CHANGING - E. R. Kirkolup; I. V. Kharlamov (Вестник СибАДИ, 2019)
Introduction. Law changes concerning road service and cargo traffic rules lead to the necessity of maximal axel load calculating during the cargo transportation. Such problem is particularly important while friable cargo transporting, as accelerating or breaking cargoes (road-trains) at a longitude inclination or turning could provoke partial lading shift towards the cargo axles. The paper demonstrates the results of friable cargo offset experimental research (grail, broken stone) while transporting. Moreover, the authors also describe influence of the friable cargo offsets on freight transport axle load changing.Materials and methods. The research measured friable cargo level in the road-train semitrailer before and after the experiment, axle weighting and the full mass weighting. In addition, the authors made video filming of friable cargo offsets.Results. Analyzing the experimental data of axial weighting, the authors noted that during the friable cargo transportation, the cargo was redistributed inside the semitrailer and such process led to a change in axial loads of the road-train. The axel load changing was not included into the measurement accuracy and was about 1,4 – 4,9%. Another argument of the friable cargo shift inside the semitrailer was cargo video filming while transporting. Video analysis showed that both chip stone and gravel was moving inside the semitrailer while the road-train accelerated motion.Discussion and conclusions. As a result, the research proves the experimental verification of the friable cargo offset over the semitrailer ramps while braking. Such offsets lead to the changing of freight transport axle load.